Differentiated instruction: a quran-based literacy learning model in inclusive classrooms - Wachidah, Kemil; M. Solehuddin; Syihabuddin (Universitas Kanjuruhan Malang, 2025)
Primary school teachers' understanding of literacy learning is often limited to reading and writing skills, whereas 21st century literacy skills include comprehension, analysis of information, and expression of emotions and thoughts. This study developed a model of Qur'an-based Differentiated Literacy Learning using the ADDIE development method, which involved observations, interviews and questionnaires. The model goes through five stages: analyzing learners' needs and characteristics, designing Qur'an-integrated learning, developing strategies and materials, implementing in trials, and evaluating learning outcomes and socio-emotional intelligence. The results showed that the model not only significantly improved students' literacy, but also strengthened their social-emotional intelligence, as seen from increased participation and positive interactions inside and outside the classroom. The model was rated as highly feasible and practical by experts. The results of this study make an important contribution to literacy learning that is holistic and based on the moral and spiritual values of the Qur'an.